Moderating Effects of Religiosity on Predictors of Psychological Well-Being Among Older Malay Muslims - Momtaz, Yadollah Abolfathi (2010)
Malaysia, an Islamic country in South East Asia, is experiencing the population aging phenomenon. The existing body of knowledge on the predictors of psychological well being, as one of the most important indicators of aging well, is limited to western cultures and with inconclusive findings. The overall purposes of this thesis were to identify factors contributing to psychological well-being as well as examine moderating effect of religiosity on the psychological well-being of elderly Malays. The sample for this study was a subset of 1415 older Malay Muslims, obtained from a cross-sectional survey entitled “Patterns of Social Relationship and Psychological Well-being among Older Persons in Peninsular Malaysia” which conducted from 2007 to 2009. Data analysis was conducted with “The Statistical Package for Social Sciences” (SPSS 13) and the“ModGraph-2” software program. A multiple regression analysis and two 4-step moderated hierarchical regression analyses were used to test hypotheses. The mean psychological well-being score of the respondents was 62.3 (SD=22.54). Majority of the respondents (66.1%) reported good psychological well being. Using multiple regression analysis a significant model emerged (F (11, 1402) =23.96, p≤.001, R2=.16), where social support and physical health as well as age, household income, sex, and marital status significantly contributed to the prediction of psychological well being. Next, two 4-step moderated hierarchical regression analyses were conducted to examine the moderating effects of religiosity. The first 4-step moderated hierarchical regression analyses revealed that social religiosity (Beta=.07, p≤.01) and personal religiosity (Beta=.06, p≤.05) significantly moderate relationship between physical health decline and psychological well being. The second 4-step moderated hierarchical regression analyses revealed that only social religiosity (Beta=.07, p≤.01) statistically moderates relationship between social isolation and psychological well being. The results provide both theoretical and practical implications. Theoretically, findings supported and extended the Social Production Function Theory of psychological well-being by adding religiosity as a moderating factor to attenuate negative effects of age related changes on psychological well-being in later life. From the practical perspective, social and health policy makers should pay special attention and provide opportunities to vulnerable elderly groups to poor psychological well-being including older women, widowed, the poor, socially isolated, chronically ill older persons, and the oldest old. Another important practical implication is that social workers, counselors and other mental health professionals working with older persons should integrate religiosity as an important resource into their therapeutic work for the development and maintenance of psychological well-being of older persons facing age related problems.